2019
DOI: 10.1055/a-0903-2938
|View full text |Cite
|
Sign up to set email alerts
|

Real-world biologic treatment and associated cost in patients with inflammatory bowel disease

Abstract: Objectives This study aimed to describe biologic treatment of German inflammatory bowel disease (IBD) patients, including biologics’ dosage, health care resource use, and treatment-associated cost. Methods In this retrospective claims data analysis, all continuously insured adult IBD patients (Crohnʼs disease [CD] or ulcerative colitis [UC]) who started a new therapy with an anti-tumor necrosis factor alpha (anti-TNF-α) or vedolizumab (VDZ) were included. Observation started with the date of the firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 16 publications
1
13
0
2
Order By: Relevance
“…Interestingly, we discovered an increase in the frequency of β7 + CD4 memory T cells in blood, but a decrease of these cells in RB. These findings suggest that the administration of anti-α4β7 mAb reduced the trafficking of α4β7 hi T cells to the gut, confirming the mode of action, prevention of trafficking of activated T cells to the gut, of vedoluzimab as adjunctive therapy in inflammatory bowel disease and Crohn disease (IBD/CD) (29)(30)(31)(32)(33)(34). As such, a similar strategy is of interest in the context of HIV infection, where CD4 T cells that express CCR5 and α4β7 are the preferred target for HIV infection in the gut, a major site for early HIV infection and replication (2,(35)(36)(37).…”
Section: Discussionmentioning
confidence: 61%
“…Interestingly, we discovered an increase in the frequency of β7 + CD4 memory T cells in blood, but a decrease of these cells in RB. These findings suggest that the administration of anti-α4β7 mAb reduced the trafficking of α4β7 hi T cells to the gut, confirming the mode of action, prevention of trafficking of activated T cells to the gut, of vedoluzimab as adjunctive therapy in inflammatory bowel disease and Crohn disease (IBD/CD) (29)(30)(31)(32)(33)(34). As such, a similar strategy is of interest in the context of HIV infection, where CD4 T cells that express CCR5 and α4β7 are the preferred target for HIV infection in the gut, a major site for early HIV infection and replication (2,(35)(36)(37).…”
Section: Discussionmentioning
confidence: 61%
“…From 2010 to 2018, sales volume for infliximab and adalimumab increased over two-fold, and 1.8-fold for etanercept (see Figure 1 ). The rise in the sales volume of TNFα inhibitors has been attributed to several factors (e.g., the lower threshold at which treatment with biologics is initiated, changes in the dosing regimen) [ 24 , 25 ]. In the case of infliximab and etanercept, the data in this study showed that year-over-year increases (%) in use occurred shortly after biosimilar entry (13.4% increase for infliximab and 13.7% increase for etanercept).…”
Section: Resultsmentioning
confidence: 99%
“…In consequence, patients with mild disease who did not require treatment with IS or systemic corticosteroids (CS) have been excluded. Further, all patients who received a biologic during the index or follow-up period were excluded, as treatment with biologics was already analyzed in a recent study based on the same dataset [17]. Patients with prescriptions of calcineurin inhibitors were also excluded as this is a last-line treatment after biologics in most cases.…”
Section: Methodsmentioning
confidence: 99%
“…Several previous studies addressed the real-world treatment of moderate-to-severe IBD patients receiving biologic therapies [12][13][14][15][16]. However, in Germany as in most other western European countries, the majority of IBD patients are treated with conventional non-biologic therapies [17]. Treatment with non-biologic drugs has not been studied in detail over the recent years.…”
Section: Introductionmentioning
confidence: 99%